Experimental investigation on the effect of tangential force on wear and rolling contact fatigue behaviors of wheel material. (December 2015) - He, C.G.; Huang, Y.B.; Ma, L.; Guo, J.; Wang, W.J.; Liu, Q.Y.; Zhu, M.H.
Abstract: The study aims to explore the effect of tangential force on wear and rolling contact fatigue (RCF) behaviors of wheel material using a JD-1 wheel/rail simulation facility. The normal, tangential and lateral forces between the wheel/rail rollers are controlled, and the magnetic power brake was used to generate the tangential forces (16–330 N). The results indicate that the surface hardness and wear loss of wheel rollers increase with the tangential force increasing. The surface cracks mouths are perpendicular to the resultant directions of the frictional forces. There are visible secondary cracks and multilayer cracks and the interlayer material of multilayer cracks are easy to break. The compositions of wear debris consist of Fe2 O3, Fe3 O4 and iron. Highlights: The described test rig can produce RCF cracks similar to cracks observed in wheels. The tangential force plays a vital role on the wear and RCF of wheel material. The surface cracks mouths are perpendicular to the resultant direction of forces. It illustrates how multilayer cracks are built up with tangential force increasing.